Restorative Justice in the Implementation of Diversion Against Victims of Child Crimes - Ibrahim Fikma Edrisy; Kamilatun (LEGAL BRIEF, 2022)
Law Number 11 of 2012, concerning the Children's Criminal Justice System, emphasizes that at the level of investigation, prosecution, and examination of children's cases in district courts, diversion must be sought, which is carried out if the criminal act committed is threatened with imprisonment under 7 (seven) years and does not constitute a repeat of a criminal act. The purpose and usefulness of this study are to determine (1) the concept of restorative justice from the perspective of child protection and (2) Factors Inhibiting Restorative Justice like the Implementation of Diversion against Victims of Child Crimes. The approach method in this study uses a normative approach, namely by using legislation n because what will be studied are various legal rules that are the focus of this study. Based on the study results, it was concluded that restorative justice is carried out to prevent the repetition of criminal acts committed by children and keep children away from the negative influences and implications of the judicial process. The implementation of restorative justice in the perspective of child protection refers to legislation. Meanwhile, the Factors Inhibiting Restorative Justice in the Implementation of Diversion against (1) Victims of Child Crimes are coordination between agencies that carry out diversion at the investigation level, (2) understanding of the meaning of diversion, (3) lack of public trust in the rules for implementing diversion and (4) regulations regarding supervision of the implementation of the results of diversion agreements.